Ekonomi Kreatif di Masa Adaptasi Kebiasaan Baru: Kajian Kreativitas dan Inovasi Pada UMKM Subsektor Kuliner - Muhammad Hasan; Annur Fitri Hayati; Miranda Miranda; Fira Ayu Sasmita; Muh. Rijal Shafar (Universitas Negeri Padang, 2021)
This study aims to reveal the creativity and innovation of SMEs in the culinary sub-sector in Makassar City, when viewed from the perspective of the creative economy in the new adaptation period. This study is a study with a quantitative descriptive approach with survey techniques. There are four aspects measured in this study, namely the adaptation of new habits, the creativity of the culinary sub-sector MSME actors, the innovation of the culinary sub-sector MSME actors, and the marketing strategy carried out by the culinary sub-sector MSME actors. The data collection instrument used a questionnaire. Sampling used a purposive sampling technique by setting specific criteria as a condition for determining the sample so that a sample of 30 SMEs in the culinary sub-sector was obtained. The findings of this study show that even though they have faced a big storm that has shaken their economy, the culinary sub-sector MSME actors still maintain their business existence in order to be able to survive during the COVID-19 pandemic. It is proven that the culinary sub-sector MSME actors have creativity and innovation by adapting to new habits through the use of technology in business management and marketing strategies, and complying with health protocols to local government regulations.